On selenium deficiency in Graves’ disease patients with autoimmune ophthalmopathy (Ukrainian Journal of Ophthalmology, 2025)
Background: The role of selenium (Se) deficiency in the development of thyroid associated ophthalmopathy has been actively debated in the literature. The question is still debated in Ukraine due to the absence of data both on selenium deficiency in this country and blood selenium levels in Graves’ disease patients with autoimmune ophthalmopathology (AO).Purpose: To investigate blood selenium levels in Graves’ disease patients with AO.Materials and Methods: Fifty-seven Graves’ disease patients were included in the study. Of these, 44 had AO. Clinical severity of AO was classified using the NOSPECS. Of the 44 patients with AO, 16, 19 and 9 patients had class 2b, class 3a or 3b, and class 4a, respectively. All patients were euthyroids receiving antithyroid therapy (mean TSH level, 1.36 ± 0.4 mIU/L; reference TSH range, 0.4 mIU/L to 4.0 mIU/L). A Hitachi MPF-2A fluorescence spectrophotometer was used to determine blood selenium levels. A blood selenium level between 75 and 120 μg/l was considered normal, between 50 and 75 μg/l was moderate Se deficiency, and 0.05). Therefore, it may be assumed that selenium deficiency is not a factor affecting the development of AO in Graves’ disease. Finally, given that fact that 34% of Graves’ disease patients with AO exhibited no selenium deficiency, such patients should not be prescribed selenium agents without first checking their blood selenium levels.
Keywords: Graves’ disease; autoimmune ophthalmopathy; selenium